GWAS reveals novel loci and identifies a pentatricopeptide repeat-containing protein (CsPPR) that improves low temperature germination in cucumber - Li, Caixia; Dong, Shaoyun; Beckles, Diane M.; Liu, Xiaoping; Guan, Jiantao; Gu, Xingfang; Miao, Han; Zhang, Shengping (Frontiers in Plant Science, 2023)
Low temperatures (LTs) negatively affect the percentage and rate of cucumber (Cucumis sativus L.) seed germination, which has deleterious effects on yield. Here, a genome-wide association study (GWAS) was used to identify the genetic loci underlying low temperature germination (LTG) in 151 cucumber accessions that represented seven diverse ecotypes. Over two years, phenotypic data for LTG i.e., relative germination rate (RGR), relative germination energy (RGE), relative germination index (RGI) and relative radical length (RRL), were collected in two environments, and 17 of the 151 accessions were found to be highly cold tolerant using cluster analysis. A total of 1,522,847 significantly associated single-nucleotide polymorphism (SNP) were identified, and seven loci associated with LTG, on four chromosomes, were detected: gLTG1.1, gLTG1.2, gLTG1.3, gLTG4.1, gLTG5.1, gLTG5.2, and gLTG6.1 after resequencing of the accessions. Of the seven loci, three, i.e., gLTG1.2, gLTG4.1, and gLTG5.2, showed strong signals that were consistent over two years using the four germination indices, and are thus strong and stable for LTG. Eight candidate genes associated with abiotic stress were identified, and three of them were potentially causal to LTG: CsaV3_1G044080 (a pentatricopeptide repeat-containing protein) for gLTG1.2, CsaV3_4G013480 (a RING-type E3 ubiquitin transferase) for gLTG4.1, and CsaV3_5G029350 (a serine/threonine-protein kinase) for gLTG5.2. The function for CsPPR (CsaV3_1G044080) in regulating LTG was confirmed, as Arabidopsis lines ectopically expressing CsPPR showed higher germination and survival rates at 4C compared to the wild-type, which preliminarily illustrates that CsPPR negatively regulates cucumber cold tolerance at the germination stage. This study will provide insights into cucumber LT-tolerance mechanisms and further promote cucumber breeding development.